Margaret Webster papers - Webster, Margaret, 1905-1972.; Webster, Margaret, 1905-1972.; Webster, Margaret, 1905-1972.
Correspondence, lectures, articles, prompt copies of plays and operas, musical scores, set and staging diagrams, research materials, family papers, scrapbooks of clippings, printed matter, photographs, and other papers consisting primarily of material used by Webster in compiling two family biographies and reflecting her career in American theater. Documents her involvement with Eva Le Gallienne and Cheryl Crawford in the American Repertory Theater in New York, N.Y., and her interest in experimental theater with Margaret Webster Shakespeare Company (also known as Marweb Productions). Also documents Webster's service as a U.S. State Dept. specialist in South Africa. Family papers relate chiefly to the professional careers of her parents, Benjamin Webster and Dame May Whitty, on the British stage, and include genealogical material for the Webster and Whitty families. Subjects include theater in Great Britain, South Africa, and the United States; the Actors' Equity Association; ANTA (American National Theatre and Academy; apartheid; and blacklisting. Includes drafts and related material for Webster's family biographies, The Same Only Different; Five Generations of a Great Theatre Family (1969) and Don't Put Your Daughter on the Stage (1972), and notes for her technical work Shakespeare without Tears (1942).
Playwrights represented include Anton Pavlovich Chekhov, Henrik Ibsen, Eugene O'Neill, Bernard Shaw, Thornton Wilder, and Tennessee Williams. Correspondents include Brooks Atkinson, Marlon Brando, Noel Coward, Lynn Fontanne, Graham Greene, Eva Le Gallienne, Alfred Lunt, Bernard Shaw, Walter Slezak, Dame Sybil Thorndike, and Alexander Woollcott.
Library of Congress Prints and Photographs Division.
Actress, theatrical producer, author, and lecturer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Atkinson, Brooks, -- 1894-1984 -- Correspondence; Brando, Marlon -- Correspondence; Chekhov, Anton Pavlovich, -- 1860-1904.; Coward, Noel, -- 1899-1973 -- Correspondence; Crawford, Cheryl, -- 1902-1986.; Fontanne, Lynn -- Correspondence; Greene, Graham, -- 1904-1991 -- Correspondence; Ibsen, Henrik, -- 1828-1906.; Le Gallienne, Eva, -- 1899-1991.; Le Gallienne, Eva, -- 1899-1991 -- Correspondence; Lunt, Alfred -- Correspondence; O'Neill, Eugene, -- 1888-1953.; Shakespeare, William, -- 1564-1616.; Shaw, Bernard, -- 1856-1950.; Shaw, Bernard, -- 1856-1950 -- Correspondence; Slezak, Walter, -- 1902-1983 -- Correspondence; Thorndike, Sybil, -- Dame, -- 1882-1976 -- Correspondence; Webster, Benjamin, -- 1864-1947.; Whitty, May, -- Dame, -- 1865-1948.; Wilder, Thornton, -- 1897-1975.; Williams, Tennessee, -- 1911-1983.; Woollcott, Alexander, -- 1887-1943 -- Correspondence; Webster family; Whitty family; United States. -- Department of State; Actors' Equity Association; American Repertory Theater (New York, N.Y.); ANTA (Organization); Margaret Webster Shakespeare Company; Apartheid; Blacklisting of entertainers; Experimental theater; Theater; Theater -- Production and direction; Theater -- Great Britain; Theater -- New York (State) -- New York; Theater -- South Africa; Theater -- United States; Actresses; Authors; Lecturers; Theatrical producers